Determination of biomarkers associated with neoadjuvant treatment response focusing on colibactin-producing Escherichia coli in patients with mid or low rectal cancer: a prospective clinical study protocol (MICARE). Issue 12 (2nd December 2022) - Taoum, Christophe; Carrier, Guillaume; Jarlier, Marta; Roche, Gwenaelle; Gagniere, Johan; Fiess, Catherine; De forges, Helene; Chevarin, Caroline; Colombo, Pierre-Emmanuel; Barnich, Nicolas; Rouanet, Philippe; Bonnet, Mathilde
Abstract : Introduction: The management of mid and low rectal cancer is based on neoadjuvant chemoradiotherapy (CRT) followed by standardised surgery. There is no biomarker in rectal cancer to aid clinicians in foreseeing treatment response. The determination of factors associated with treatment response might allow the identification of patients who require tailored strategies (eg, therapeutic de-escalation or intensification). Colibactin-producing Escherichia coli (CoPEC) has been associated with aggressive colorectal cancer and could be a poor prognostic factor. Currently, no study has evaluated the potential association between intestinal microbiota composition and tumour response to CRT in mid and low rectal cancer. The aim of this study is to assess the association between response to neoadjuvant CRT and faecal intestinal microbiota composition and/or CoPEC prevalence in patients with mid or low rectal cancer. Methods and analysis: This is a non-randomised bicentric prospective clinical study with a recruitment capacity of 200 patients. Three stool samples will be collected from participants with histological-proven adenocarcinome of mid or low rectum who meet eligibility criteria of the study protocol: one before neoadjuvant treatment start, one in the period between CRT end and surgery and one the day before surgery. In each sample, CoPEC will be detected by culture in special media and molecular (PCR) approaches. The global microbiota composition will be also assessed by the bacterial 16S rRNA gene sequencing. Neoadjuvant CRT response and tumour regression grade will be described using the Dworak system at pathological examination. Clinical data and survival outcomes will also be collected and investigated. Ethics and dissemination: MICARE was approved by the local ethics committee (Comité de Protection des Personnes Sud-Est II, 18 December 2019. Reference number 2019-A02493-54 and the institutional review board. Patients will be required to provide written informed consent. Results will be published in a peer reviewed journal. Trial registration number: NCT04103567 .